PENGARUH MALL IMAGE TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER VALUE DAN CUSTOMER RETENTION SEBAGAI VARIABEL INTERVENING PADA MALL UPPER CLASS DI SURABAYA - Felania Felania (Jurnal Strategi Pemasaran, 2016)
This research aims to analyze the impact of Mall Image towards Customer Loyalty with Customer Value and Customer Retention as an intervening variable in Upper Class Mall in Surabaya. This research will be conducted by distributing questionnaires to 120 respondents which are visitor Galaxy Mall, Grand City, Tunjungan Plaza and Ciputra World. Quantitative analysis with path analysis analysis model method were used for the technical analysis.The results of this study indicate that the mall image influence positively and significantly related to customer value, mall image affect positively and significantly related to customer retention, customer value in a positive and significant impact on customer retention, customer value in a positive and significant impact on customer loyalty, customer retention in a positive and significant impact on customer loyalty.